2007
DOI: 10.1016/j.jasms.2007.08.009
|View full text |Cite
|
Sign up to set email alerts
|

High surface area of porous silicon drives desorption of intact molecules

Abstract: The surface structure of porous silicon used in desorption/ionization on porous silicon (DIOS) mass analysis is known to play a primary role in the desorption/ionization (D/I) process. In this study, mass spectrometry and scanning electron microscopy (SEM) are used to examine the correlation between intact ion generation with surface ablation and surface morphology. The DIOS process is found to be highly laser energy dependent and correlates directly with the appearance of surface ions (Si n ϩ and OSiH ϩ ). A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
84
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 22 publications
6
84
0
Order By: Relevance
“…40), 46), 54) Among these factors, the laser-induced rapid temperature increase of the SALDI substrate has been widely regarded as the thermal desorption of analyte molecules without thermal decomposition in organic matrix-free LDI-MS.…”
Section: Laser Threshold For Titania-based Saldi-msmentioning
confidence: 99%
“…40), 46), 54) Among these factors, the laser-induced rapid temperature increase of the SALDI substrate has been widely regarded as the thermal desorption of analyte molecules without thermal decomposition in organic matrix-free LDI-MS.…”
Section: Laser Threshold For Titania-based Saldi-msmentioning
confidence: 99%
“…AFM analysis revealed that the ␣-Si coating layer was slightly rougher on top of the hybrid, rms roughness being 0.4 nm on top of the hybrid compared with 0.1 nm on top of both silicon and SiO 2 , which might contribute toward improved ionization by several roughness related ionization mechanisms [17]. Another possible contributing factor is related to surface restructuring and melting [8,22], which has been claimed to be a key factor in the desorption process in SALDI. We observed that on the ␣-Si coated hybrid surface, clear marks were created upon exposure to the laser even at fluences that were not able to leave any visible marks on the Si and SiO 2 substrates.…”
Section: Substrate Materialsmentioning
confidence: 99%
“…Low thermal conductivity helps confine the heat [8] near the surface, but high thermal conductivity at the surface has been claimed to be conducive for transferring energy from the surface to the analytes [20]. The absorbed laser light then heats the surface, which has been identified to play a key role in the desorption process [17,21,22]. Thermal evaporation of the analyte and residual solvents has been suggested to be the desorption mechanism on porous silicon [21], but recently the role of thermally activated morphologic transitions have been emphasized by Northen et al [22], who note that the ionization threshold typically does not depend on the properties of the analyte, as would be expected for a strictly thermal desorption process.…”
mentioning
confidence: 99%
See 2 more Smart Citations